Transcriptional elongation and alternative splicing - Dujardin, Gwendal (2013)
Alternative splicing has emerged as a key contributor to proteome diversity, highlighting the importance of understanding its regulation. In recent years it became apparent that splicing is predominantly cotranscriptional, allowing for crosstalk between these two nuclear processes. We discuss some of the links between transcription and splicing, with special emphasis on the role played by transcription elongation in the regulation of alternative splicing events and in particular the kinetic model of alternative splicing regulation. This article is part of a Special Issue entitled: RNA polymerase II Transcript Elongation.